INTEGRATION OF THE SEHAT-LINGKUNGAN MODEL INTO QUALITY AND ACCREDITATION SYSTEMS: A CASE STUDY OF ENVIRONMENTAL HEALTH RISK MANAGEMENT AT THE MUNA DISTRICT HEALTH CENTRE: SEHAT-LINGKUNGAN MODEL - Kirana, Candra; Putri , Usti Syah; Rauf, Muhammad Abdul (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2025)
Background: Environmental health management in health care facilities is an important determinant in ensuring service quality and patient safety. Community health centres in Muna Regency face real challenges in the form of non-standardized medical waste management, limited water quality monitoring, and inadequate basic sanitation facilities. Previous research emphasizes the importance of water, sanitation, and hygiene (WASH) in primary care accreditation, but the integration of environmental health indicators into the quality system of health centre in Indonesia has rarely been studied, especially in resource-limited areas. Methods: This study used a qualitative approach with a case study design in three Health centre (Kabawo, Katobu, and Tampo) through in-depth interviews, field observations, and document reviews. Results: The results show that the dominant weaknesses in each health centre are different: Kabawo faces problems in medical waste management, Katobu in the consistency of clean water monitoring, and Tampo in limited sanitation infrastructure, all of which have a direct impact on accreditation scores. Conclusion: These findings confirm the relevance of integrating the Environmental health  Model into the primary service quality system as an adaptive strategy that can strengthen health policies, improve human resource capacity, and encourage the achievement of accreditation quality standards in areas with limited resources.